Stagnation point flow over a stretching sheet with Newtonian heating - Muhammad Khairul Anuar Mohamed,; Mohd. Zuki Salleh,; Roslinda Nazar,; Anuar Ishak, (Universiti Kebangsaan Malaysia, 2012)
In this study, the numerical solution of stagnation point flow over a stretching surface, generated by Newtonian heating in which the heat transfer from the surface is proportional to the local surface temperature is considered. The transformed boundary layer equations are solved numerically using the shooting method. Numerical solutions are obtained for the local heat transfer coefficient, the surface temperature and the temperature profiles. The features of the flow and heat transfer characteristics for various values of the Prandtl number, stretching parameter and conjugate parameter are analyzed and discussed.